Chicago Economics: Permanence and Change - Reder, Melvin W. (Journal of Economic Literature, 1982)
M Y PERCEPTION of Chicago economics is that of participant-observer. As a working economist at Chicago, I have observed other members of the tribe at close hand, and have obtained their critical reactions to this description of their intellectual outlook and styles of work.' The perceptions of any participant-observer are conditioned, however, by his position in time and in the institutional configuration. My vantage points have been those of a graduate student in the Economics Department, of an assistant and personal friend of Oscar Lange from 1939-41, and of a Professor in the Graduate School of Business since 1974. Yet another source of perspective bias is field of specialization. As a graduate student, my primary interests were Pure Theory, Welfare Economics and Macroeconomics; my present focus is upon Labor Economics, with Industrial Organization a secondary interest. This pattern of specialization determines the workshops that I regularly attend, the manuscripts that I read and the individuals with whom I am in close contact. The influence of specialty upon one's perspective of Chicago economics is not trivial. In preparing this essay, I have found that our Chicago corner of the economics profession can look quite different to someone in Monetary Theory or International Trade than to a specialist in Labor, Industrial Organization or Law and Economics. This essay does not pretend to be an exhaustive account of Chicago economics during the past half century. It is primarily an attempt to describe the evolution of a few basic ideas associated with a particular institution. The focus is upon ideas rather than their protagonists or the institution whose name is their generic label. Describing these ideas is not easy because their central tendency has changed 1 Manifestly, this paper is a personal statement for which no one but the author is responsible. However, I have had far more than normal critical input from friends and colleagues at Chicago and elsewhere. My Chicago associates have served in the dual capacity of information sources and critics: George Stigler's contributions are acknowledged in footnotes, though inadequately, and I have also benefitted from the comments of Jacob Frenkel, David Galenson, Robert Lucas, Merton Miller, George Neumann, Peter Pashigian, Sam Peltzman, and T. W. Schultz. Among the non-Chicago friends who have made especially helpful suggestions are: Kenneth Arrow, Martin Bronfenbrenner, Albert Rees, and the editor. My readers have been unanimous in urging reduction in over-all length, but virtually all of them also suggested small additions. Of course, most of their suggestions would have improved the final product, if only I had had the skill to implement them. Lacking this, I have been compelled to omit discussion of many important ideas and persons. Also, I have not had space to relate the discussion of this paper to previous discussions of Chicago economics such as Warren J. Samuels (1976), Bronfenbrenner (1962), A. W. Coats (1963), Miller (1962), and Stigler (1962a). My only defense for these sins of omission is lack of space and inability to organize better.